2023
DOI: 10.3389/fpubh.2023.1087248
|View full text |Cite
|
Sign up to set email alerts
|

Physical performance and muscle strength rather than muscle mass are predictor of all-cause mortality in hemodialysis patients

Abstract: ObjectivesPatients undergoing maintenance hemodialysis usually suffer a high burden of poor functional status. The aim of this study was to investigate the association between muscle mass, muscle strength as well as physical performance with all-cause mortality in hemodialysis patients.Methods923 hemodialysis patients (565 men, mean aged 61.3 ± 12.7 years) were included from eight facilities in Tianjin and Shanghai of China from 2019 to 2021. Muscle mass was evaluated by skeletal muscle index (SMI) and muscle … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 32 publications
0
4
0
Order By: Relevance
“…To ensure accuracy, postgraduate students in the eld of physical health, who had received specialized training, conducted all assessments using a standardized protocol. Furthermore, to minimize potential errors, each functional assessment item was assigned to a speci c personnel member for data collection across all participants [12].…”
Section: Physical Performancementioning
confidence: 99%
“…To ensure accuracy, postgraduate students in the eld of physical health, who had received specialized training, conducted all assessments using a standardized protocol. Furthermore, to minimize potential errors, each functional assessment item was assigned to a speci c personnel member for data collection across all participants [12].…”
Section: Physical Performancementioning
confidence: 99%
“…Longitudinal studies have shown that the decline in muscle strength occurs more rapidly than the loss of muscle mass, suggesting that factors other than muscle mass contribute to the loss of muscle strength ( 33 , 34 ). Moreover, physical performance and muscle strength, rather than muscle mass, are predictors of all-cause mortality in ESRD patients ( 11 , 35 ). However, there is a lack of longitudinal studies.…”
Section: Clinical Features Of Muscle Mass and Function In Patients Wi...mentioning
confidence: 99%
“…Chen et al . [ 17 ] found that muscle strength is more closely related to mortality than muscle mass. HGS is connected to mental and physical QOL in community-dwelling elderly people, according to Laudisio et al .…”
Section: Introductionmentioning
confidence: 99%